PENGARUH KOMPETENSI DAN WORK PERFORMED AUDITOR INTERNAL TERHADAP JUDGEMENT AUDITOR EKSTERNAL DALAM PERENCANAAN AUDIT - Maylia Pramono Sari (Fakultas Ekonomi Universitas Pekalongan, 2015)
In providing judgement, the external auditor would issue a large audit fee and a long time for a given goodquality judgment. One solution to reduce costs and time required audit, the external auditors to cooperate withthe internal auditors of the company. This study aims to determine whether the competence and workperformed internal auditor judgment affect the external auditors in the audit planning on KAP of Semarang.The population in this study are the external auditors who work in public accounting firm in the city ofSemarang. Sampling using a convenience sampling amounted to 37 people. The independent variables in thisresearch are Competency Internal Auditors (X1), Performed Work of Internal Auditors (X2), while thedependent variable (Y) is judgment External Auditor in Audit Planning. Methods of data collection using thequestionnaire method. The method of analysis used descriptive analysis and multiple linear regression analysiswith SPSS program.The results showed that the competence and the work of internal auditors performed simultaneously affect thejudgment external auditor in planning the audit. Partially competence of internal auditors have a significanteffect on judgments of external auditors in planning the audit. Work performed while the internal auditors havea significant impact on the external auditor judgment in planning the audit.This research is expected to be useful in implementing the external auditor for the audit program. Due to thecooperation with the company's internal auditors, external auditors can save time and audit costs withoutreducing the quality of judgments given against the company's external auditors.Keywords: External Auditors Judgement, Competence of Internal Auditors,Internal Auditor Work Perfo rmed